Attitudes toward smoking of smokers and non-smokers - Tokay Argan, Mehpare (Journal of Dependence, 2009)
Objective: The purpose of this study is to find out the smoking attitudes, and smoking behavior of people who live in Bilecik.Method: This descriptive study was carried out among 795 people who live in Bilecik. Socio-demographic characteristics, smoking status, attitutes toward smoking, and smoking quit intend of respondents were examined. Statistical analyses were performed using the SPSS software packages. ANOVA and t test were applied to asses the demographics differentiations of the attitudes factors toward smoking.Results: The results of this study indicated that five factors were about attitudes toward smoking of smokers and non-smokers. These are the health effect, psychological effect, social acceptence (effect), environmental and money allocated from individuals' budgets to smoking, and family effect. According to smoking behavior of participators, %49.1 are non-smokers, % 37.2are daily-smokers, %13.7 are occasional smokers. The %48.8 of daily-smokers are willing to stop smoking in a one year period. The %62.2 of occasional smokers are willing to stop smoking in a one year period.Conclusion: The results of the regression analysis indicated that the regression model was statistically significant, and %14 of the overall smoking quit intension of daily-smokers and occasionally smokers was explained by the five factors of attitudes toward smoking. Attitudes factors toward smoking were found significantly different according to demographic characteristics of participators.
Keywords: Smoking; smoking attituted; smoking status; smoking quit intension